A NUMERICAL STUDY OF THE EFFECT OF A BELOW-WINDOW CONVECTIVE HEATER ON THE HEAT TRANSFER RATE FROM A COLD RECESSED WINDOW - P. Oosthuizen (Chemical Engineering Transactions, 2009)
Abstract preview not available - see full-text PDF article.